Radical practices, radical pedagogies: intercultural explorations in language and meaning. Issue 4 (December 2022) - Alexander, Jacqui; Grassi, Samuele; Mellos, George
Abstract : This article reflects on the visual, spatial, and textual devices deployed by the Architettura Radicale in the 1960s and 1970s through a discussion of a pedagogical project developed for undergraduate architecture students from Monash University, Australia, as part of a travelling intensive based in Prato, Italy. At the time, Prato became the subject of debate about the rapid expansion of consumer culture in Italy, as underscored in Claudio Greppi's graduating project, 'Territorial City-Factory' (1964-5). This architectural proposal rendered the area between Prato and Florence as a totalising city-factory, a proposition that was later developed under Archizoom as 'No-Stop City' (1968-70). Greppi's recasting of Prato as a site for political and architectural experimentation became the catalyst for a teaching-led research project, re-examining the work of the Radical movement in Tuscany. In collaboration with architect and artist Gianni Pettena, the intensive sought to draw out the performative and embodied approaches implicit in his own work and that of his peers including UFO and 9999, as well as the rhetorical devices embedded within the critical fictions of Superstudio and Archizoom. By first dissecting and then redeploying these techniques in response to a site-specific brief, the ultimate pedagogical aim was to expose the students to an expanded range of architectural approaches and to re-evaluate the nature of radical practices 'within and against' the omnipresent struggles of late capitalism, and the contemporary cultural and educational context of neoliberalism and the university.